Flood occurrence, smart tunnel operating system and traffic flow: A case of Kuala Lumpur smart tunnel Malaysia - Isah, Nuhu (2016)
Managing environmental disaster requires the use of technology into how technology is used to minimize the casualties and loss incurred when disaster strikes. This research study the relationship between SMART tunnel maintenance works, flooding and traffic flow management. SMART is an acronym for “Stormwater Management and Road Tunnel”. This project is located in Kuala Lumpur the capital metropolitan city of Malaysia. The SMART Tunnel project was initiated by the Former Prime Minister Tun Dr. Mahathir Mohammad under the Malaysian Development Plan. The project was a joint venture project between the government and the private sector corporation. This study investigates the relationships between SMART Tunnel maintenance works, flooding and traffic flow in Kuala Lumpur City Centre. Malaysia. The study adopted quantitative and qualitative approaches. Ten respondents were interviewed to achieve the research objectives, where eight of them are from Drainage and Irrigation Department, while the remaining two are from the Malaysian Highway Authority. Correlation and percentage value analysis were used to achieve the research objectives. The study reported that there are significant relationships between SMART Tunnel maintenance works with flood occurrences and SMART Tunnel maintenance work with traffic flow. When there is enough maintenance works, flood occurrence will be very low and vice versa. The research shows that SMART Tunnel plays an important role in decongestion of traffic to and from the Kuala Lumpur City Centre. It diverts approximately 30,000 cars a day. This research contributes in providing valuable frontier and offers means to improve the maintenance works of SMART Tunnel to optimize the utilization on flood disaster and traffic flow management in Kuala Lumpur City Centre. It also updates people about the roles of SMART Tunnel in Kuala Lumpur City Centre.